Pierre St. Germain (1790-1843?) - Houston, C. Stuart (ARCTIC, 1986)
Of the fifteen hired men on John Franklin's first land expedition, Pierre St. Germain has been the most underrated. Although a rogue, a rebel, and a troublemaker, he was the strongest, most resourceful, and most versatile man on the expedition. . St. Germain, part French and part Indian, served in the Athabasca district for the North West Company from 1812 to 1818. In 1819 he joined the Hudson's Bay Company at a wage of 2,000 Montreal livres (100 Pounds Sterling) per annum and served as an interpreter at Fort Resolution, Great Slave Lake. . On 5 June 1820, Colin Robertson wrote McVicar, giving permission for St. Germain to join the arctic land expedition under the command of Lt. John Franklin. On 25 July 1820, St. Germain entered into an agreement with Franklin for wages of "3000 Livres per annum until his return to Ft. Wedderburn." This 150 Pounds Sterling was two-and-a-half times the amount Franklin offered a French Canadian voyageur. St. Germain's employers recognized his ability but also his independent ways. Robertson described St. Germain as "an intelligent young man" and 5 June 1820 wrote "I have given up an excellent Chippeyan interpreter, St. Germain." McVicar considered him indispensable, mentioning how he could travel without either a blanket or provisions, but also noting his liking for alcohol. . Richardson considered St. Germain to be one of the most reliable men on the expedition and the one with the most influence on the accompanying Copper Indians. St. Germain was intelligent, determined, and when reasonably fed, indefatigable. He made the preliminary trip to Point Lake with Back and Hood, 29 August-10 September 1820. During the winter of 1820-21, he snowshoed 440 km from Fort Enterprise to Fort Resolution, bringing back the two Eskimos, Augustus and Junius. Strong, resourceful, practical, a man of great stamina, St. Germain was also exceedingly dexterous, evidenced by his use of a made-down canoe to cross the Burnside River on 9 September and, five days later, to ferry Franklin across Belanger ...